Enterprise Resource Planning (ERP) SAP Business One Evaluation and Improvement Recommendation using Customized Odoo - Winda Maulidina Nurrohmah; Jansen Wiratama (Ultima InfoSys : Jurnal Ilmu Sistem Informasi, 2022)
The goal of this research is to carry out and understand the evaluation of the success rate on SAP Business One, and the results of the evaluation are developed into the configuration and customization activities of the Odoo ver 15.0 open-source ERP system, because they do not have access rights to perform customization in the SAP Business One system. As a result, Odoo is one of the open-source ERP systems that can accommodate research recommendations and outcomes. The goal of this research is to determine the issues that arise throughout the company's use of the SAP Business One system. It is then anticipated to be a solution to company difficulties and to suit the firm's needs.